2014
DOI: 10.1111/echo.12537
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Long‐Term Mortality in Patients with Hypertrophic Cardiomyopathy

Abstract: Instead of the ACE genotype and activity, echocardiographic evaluation findings such as LV systolic and diastolic diameters, LV mass index, and particularly LA dimension may predict long-term mortality in patients with HCM. PAF has also significant importance in the long-term mortality in patients with HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…LVEDD was largely affected by LV filling and contraction in HCM patients. Bostan et al [13] identified LVEDD was significantly different between survivors and nonsurvivors in HCM patients (P � 0.04). Nevertheless, LVEDD was not an independent predictor in the further analysis.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…LVEDD was largely affected by LV filling and contraction in HCM patients. Bostan et al [13] identified LVEDD was significantly different between survivors and nonsurvivors in HCM patients (P � 0.04). Nevertheless, LVEDD was not an independent predictor in the further analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Both volume and pressure overload may lead to enlarged LA. Bostan et al reported that LAD ≥41 mm predicted 13-year mortality with a sensitivity of 82% and specificity of 78%, respectively [13]. Nistri et al [22] indicated LAD >48 mm was related to an HR of 1.9 for allcause mortality in HCM patients (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] found that in patients with dilated cardiomyopathy or heart failure (HF), LV dilatation was significantly associated with increased mortality [ 6 , 7 , 8 ]. In patients with hypertrophic cardiomyopathy (HCM), LVEDD was also a significant predictor of mortality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%